Modeling of generative design for wire arc additive manufacyuring (WAAM) / Wang Yazhuang - Wang, Yazhuang (2021)
Generative design is a new design method that can generate many qualified models in a short period of time, which is very innovative and convenient. As a kind of additive manufacturing technology, wire arc additive manufacturing technology has a very wide range of applications, the wire size of wire arc additive manufacturing technology determines that it can be used to manufacture special parts of generative design models. For the generative design method and wire arc additive manufacturing, the report has carried out a very detailed introduction. This research also used Autodesk Fusion360 software to explore generative design, and performed shape optimization analysis on conventional model, and then performed static stress analysis on the model after generative design and shape optimization analysis. Through the comparison of static stress analysis results, a model that is more suitable for arc additive manufacturing is selected. Finally, a generative design guide that can be manufactured by arc additivemanufacturing technology is initially explored, and future research work is prospected.